World employment and social outlook : the changing nature of jobs. (World Employment and Social Outlook., 2015)
The World Employment and Social Outlook is the ILO's new flagship report on world of work issues. Covering advanced as well as emerging and developing economies, the report documents the significant rise in new forms of work (including temporary, casual and part-time employment) and the decline in the standard employment relationship, characterized by open-ended, full-time jobs.